UTILIZATION OF SAGO FINE WASTE AS A NEW MATERIAL IN THE PROCESS OF MANUFACTURING CEMENT BRICK - ABD WAHAB, NORHAYATI; ADNAN, SURAYA HANI; MOHAMAD, MAZIZAH EZDIANI (2023)
Sago waste is a by-product of the sago starch extraction process that is typically dumped into nearby streams. In this study, sago waste that has undergone a process of physical treatment, named Sago Fine Waste (SFW), is used as a material for making cement bricks. This paper compares the mechanical properties of cement brick containing Sago Fine Waste as partial sand and cement replacement. This research aimed to determine the density, compressive strength, and water absorption test; all the specimens were cured for 7 and 28 days. The strength of cement bricks was investigated based on the difference between two water-cement ratios: 0.5 and 0.6. Brick specimens are designed with five different percentages of 0, 5, 10, 15, 20 and 25% replacement of SFW. The mortar mix is based on a ratio of 1:3, which follows Malaysian brick production standards. Based on the experimental results, the brick's density and compressive strength decrease as the Sago Fine Waste replacement increases. In contrast, water absorption increases parallel to the increment of Sago Fine Waste. Therefore, the optimum composition of Sago Fine Waste is less than 10% to get the strength set on MS 1933: Part 1: 2007. Data analysis also shows that cement replacement gives the best properties value compared to sand replacement. Replacement of 5% of cement had the highest strength of brick with 15.6 MPa at a curing age of 28 days. This shows a water-cement ratio of 0.6 enhances the brick strength owing to the pozzolanic effect of Sago Fine Waste for producing more sustainable bricks.